Prevalent transmission of 'Candidatus Liberibacter asiaticus’ over ‘Ca. Liberibacter americanus’ in a long-term controlled environment - Gasparoto, Maria Cândida de Godoy; Primiano, Isabela Vescove; Bassanezi, Renato; Lourenço, Silvia Afonseca; Montesino, Luiz; Wulff, Nelson Arno; Martins, Elaine Cristina; Bergamin Filho, Armando; Amorim, Lilian (The American Phytopathological Society (APS), 2021)
In Brazil, citrus huanglongbing (HLB) is associated with ‘Candidatus Liberibacter americanus’ (CLam) and ‘Ca. Liberibacter asiaticus’ (CLas). However, there are few studies about HLB epidemiology when both Liberibacter spp. and its insect vector, the Asian citrus psyllid (ACP, Diaphorina citri), are present. The objective of this work was to compare the transmission of HLB by ACP when both CLam and CLas are present as primary inoculum. Two experiments were performed under screenhouse conditions from April 2008 to January 2012 (experiment 1) and from February 2011 to December 2015 (experiment 2). The experiments were carried out with sweet orange plants infected with CLam or CLas as inoculum source surrounded by sweet orange healthy plants. One hundred Liberibacter-free adult psyllids were monthly confined to the source of inoculum plants for 7 days with subsequent free movement inside the screenhouse. Fortnightly, nymphs and adults of psyllids were monitored. Psyllid and leaf samples were collected periodically for Liberibacter detection by PCR or qPCR. CLas was detected more frequently than CLam in both psyllid and leaf samples. No mixed infections were detected in the psyllids. A clear prevalence of CLas over CLam was observed in both experiments. The final HLB incidences were 16.7 and 14.5% of Liberibacter-positive test plants, and CLas was detected in 92.3 and 93.1% of these infected plants. Mixed infection was observed only in 3.8% of infected test plants in experiment 1. These results endorse the shift in the prevalence of CLam to CLas observed in citrus orchards of São Paulo, Brazil.
Keywords: Asian citrus psyllid; Citrus sinensis; Comparative epidemiology; Greening